Utilization of lemon grass (Andropogon citratus) for the production of bottled iced tea - Oguis, Webster A. (2011)
Lemon grass (Andropogon citratus) was utlized for the production of unflavored (Set1) and calamansi falvored (Set 2) bottled iced tea. Both sets utilized different variations of sweeteners such as sucrose with honey (50-50), high